Development of Web-based Load Duration Curve system for analysis of total maximum daily load and water quality characteristics in a waterbody - Kim, Jonggun; Engel, Bernard A.; Park, Youn Shik; Theller, Larry; Chaubey, Indrajeet; Kong, Dong Soo; Lim, Kyoung Jae (Journal of Environmental Management, 2012)
In many states of the US, the total maximum daily load program has been widely developed for watershed water quality restoration and management. However, the total maximum daily load is often represented as an average daily pollutant load based on average long-term flow conditions, and as such, it does not adequately describe the problems they aim to address. Without an adequate characterization of water quality problems, appropriate solutions cannot be identified and implemented. The total maximum daily load approach should consider adequate water quality characterizations based on overall flow conditions rather than on a single flow event such as average daily flow. The Load Duration Curve, which provides opportunities for enhanced pollutant source and best management practice targeting both in the total maximum daily load development and in water quality restoration efforts, has been used for the determination of appropriate total maximum daily load targets. However, at least 30 min to an hour is needed for unskilled people based on our experiences to generate the Load Duration Curve using a desktop-based spreadsheet computer program. Therefore, in this study, the Web-based Load Duration Curve system (https://engineering.purdue.edu/∼ldc/) was developed and applied to a study watershed for an analysis of the total maximum daily load and water quality characteristics in the watershed. This system provides diverse options for Flow Duration Curve and Load Duration Curve analysis of a watershed of interest in a brief time. The Web-based Load Duration Curve system is useful for characterizing the problem according to flow regimes, and for providing a visual representation that enables an easy understanding of the problem and the total maximum daily load targets. In addition, this system will be able to help researchers identify appropriate best management practices within watersheds.